Advertisement Remove all ads

Factorize Each of the Following Expression: A(A − 2b − C) + 2bc - Mathematics

Sum

Factorize each of the following expression:
a(a − 2b − c) + 2bc

Advertisement Remove all ads

Solution

\[a(a - 2b - c) + 2bc = a^2 - 2ab - ac + 2bc\]
\[ = ( a^2 - ac) + (2bc - 2ab)\] [Regrouping the terms]
\[ = a(a - c) + 2b(c - a)\]
\[ = a(a - c) - 2b(a - c) [ \because (c - a) = - (a - c)]\]
\[ = (a - 2b)(a - c)\] [Taking (a - c) as the common factor]

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 8 Maths
Chapter 7 Factorization
Exercise 7.4 | Q 20 | Page 12
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×